Impact of the Congruence Between an AI Model’s Personal Life Settings and Product Characteristics on Product Attractiveness in Advertisement - Takehiro Ebitani; Takumi Kato (Maketingu rebyu)
Research on the advertising effectiveness of models has emphasized the importance of congruence between a model’s physical and internal characteristics and the product’s attributes. However, these studies have primarily focused on celebrity and non-celebrity human models. Recently, the use of AI-generated models in advertising has gained attention due to their low cost and low risk. This study addresses the research question: “Does the congruence between an AI model’s personal life setting and product characteristics enhance product attractiveness in advertising?” Randomized controlled trials (RCTs) to investigate this question showed that setting the AI model’s attributes to married with children enhanced product attractiveness in a detergent advertisement. This finding suggests that insights from previous research on celebrity and non-celebrity models can also be applied to AI models, which do not have real personal lives, thereby extending academic knowledge and providing practical implications for marketers.